Beyond the post: an SLR of enterprise artificial intelligence in social media - Maldonado-Canca, Luis; Casado-Molina, Ana María; Cabrera-Sánchez, Juan Pedro; Bermúdez-González, Guillermo José (Springer, 2024)
This study explores the impact of artificial intelligence (AI) on brand communication within corporate social networks, analyzing its benefits, ethical and technical challenges, and proposing responsible implementation strategies enriched with new theoretical contributions. To achieve this, a systematic literature review (SLR) was conducted based on the SPAR-4-SLR methodology by Paul et al. (2021), using 57 studies from Scopus and Web of Science over the past six years. This approach was complemented with recommendations from Kitchenham and Charters (2007) to ensure rigor and thoroughness in the analysis. The study reveals that artificial intelligence transforms interactions within corporate social networks by enabling effective personalization, optimizing customer experience, and enhancing satisfaction. Benefits include precise segmentation, predictive analytics, and customer service optimization through chatbots. However, significant ethical challenges also emerge, such as data privacy, algorithmic bias, and a lack of transparency in AI models. The necessity for responsible practices and regulations that foster user trust and mitigate risks associated with the implementation of AI in digital communication strategies is emphasized.
Keywords: Comunicación en la empresa; SLR; Artificial intelligence; Corporate social networks; Customer-company engagement; Digital marketing; Business communication